(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2026)
This article examines the phenomenon of judicial creation of law and the challenges inherent to its practice within the contemporary legal order. The study aims to analyze the extent to which judges, beyond applying pre-established norms, exercise a creative function in the production of legal rules—particularly when addressing legal gaps, constitutional or regulatory omissions, ambiguities, and indeterminate legal concepts. The investigation addresses judicial activism, distinguishing legitimate creative interpretation from actions that overstep the constitutional boundaries of the jurisdictional function. Ultimately, the paper identifies the guidelines and limits within which the Judiciary may create law to ensure the proper resolution of interest conflicts without compromising the separation of powers or legal certainty. To this end, it employs the hypothetical-deductive method through a theoretical, exploratory, and qualitative investigation, grounded in a review of the literature and case law. It is concluded that judicial law-making is an instrument that ensures the vitality of justice; however, it does not grant judges a license for arbitrariness or voluntarism. Therefore, the judge should intervene creatively only when the legal system proves insufficient to offer a fair and equitable resolution to the conflict.